TINGKAT KECEMASAN REMAJA DALAM PENERIMAAN VAKSIN COVID-19 - Haumeni, Wilfredo John; Elon, Yunus (Coping: Community of Publishing in Nursing; Vol 10 No 2 (2022): April 2022DO - 10.24843/coping.2022.v10.i02.p02, 2022)
Face-to-face learning has now been implemented in various schools. However, with the ongoing Covid-19 pandemic conditions, the community, especially students, still have to implement health protocols. In addition to wearing masks, washing hands, maintaining a distance of 1 meter, and limiting mobilization, carrying out Covid-19 vaccinations are steps that need to be taken. The Covid-19 vaccine is currently available for teenagers who take face-to-face learning. However, in practice, teenagers experience anxiety before and after receiving the Covid-19 vaccination. This study aims to determine the level of adolescent anxiety in receiving Covid-19 vaccination with a descriptive method with a quantitative approach. The respondents of this study were 60 teenagers who took part in face-to-face learning at Alor Adventist College in Kupang, which were obtained using purposive sampling technique. The results showed that as many as 23 people (38,3%) had moderate anxiety, 22 people (36,7%) had mild anxiety, 8 people (13,3%) were not anxious, and 7 people (11,7%) had severe anxiety. The average anxiety experienced by adolescents is in the category of mild anxiety with a mean of 49,55. Education is needed for adolescents in receiving Covid-19 vaccinations regarding handling side effects of vaccination.